Experimental characterization of diffuse speckle pulsatile flowmetry system - Choo, Tristan Wen Jie; Zhang, Ruochong; Bi, Renzhe; Olivo, Malini (Frontiers in Physics, 2022)
The recently developed Diffuse Speckle Pulsatile Flowmetry (DSPF) offers high measurement rates of around 300 Hz for non-invasive measurement of blood flow in deep tissue (up to approximately 15 mm depth), showing promising potential for the monitoring of various pathologies associated with abnormal blood flow. The effects of various parameters associated with this technique such as speckle size and exposure time on the measured flow readings, however, have yet to be studied. In this work, we examine these relationships experimentally, observing the existence of a strong inverse relationship between the number of pixels per speckle and the measured DSPF readings in no-flow setups using both static single light scattering and multiple light scattering mediums, and a strong linear relationship between exposure time and the gradient of the regression line between the actual and measured flow rates in a dynamic setup using a tissue-mimicking flow phantom. We reported how the flow measurement sensitivity was affected by these parameters. These results would enable researchers using the DSPF technique to select and utilize the most optimized settings for their specific use applications.